The Concept of Thermodynamic Law in The Perspective of Islamic Philosophy - Nopriyansa, Eko; Revi, Dhyanesh (RELIGIA, 2021)
This article aims to analyze the concept to Therodynamic law used in physics in a review of Islamic philosophy related to the concept of Tawhid or divinity. Specifically, the analysis in this research is focused on how the intersection between the laws of Termodynamics and the concept of Tawheed in Islam both in terms of thermenology in ekplaining the existence of energi. This research is a Literature research that uses data sources as awhole or mostly obtained through a review of the literature. The result of this study indicate that there is an intersection and contrasting unserstanding between the concept Thermodynamic law which is based on empirical undersanding and the concept of Tawhid in Islam which is absolute belief, such as Surah Al-Ikhlash, which believes that there is no equality of something wiht Allah, both in meaning and equality in subtance.